Micronutrient distribution and their association with soil properties in Entisols of Punjab - SHARMA, B D; AGGARWAL, V K; MUKHOPADHYAY, S S; ARORA, HARSH (The Indian Journal of Agricultural Sciences, 2014)
An investigation was carried out during 2000 to study surface and profile distribution of total and diethylenetriaminepentaacetic acid (DTPA)-extractable zinc, copper, manganese and iron in Entisols of Punjab. The soils were developed onsand-dunes, floodplains and Siwalik hills region. They showed gradual increase in the fineness of soil texture from sandduneto the mountain region and were associated with aridic, ustic and udic mo~sture regime. The soils were stratified, nearneutral to alkaline (PH 6.5 to 9.0) and calcareous. In general, total and DTPA-extractable micronutrients were higher insurface horizons and decreased in subsurface horizons. Soil taxonomic units had a influence on the spatial distribution fortotal and available content of micronutrient in these soils. The total content varied from 15 to 76 mg/kg for zinc, from 1to 31 mg/kg for copper, from 100 to 1 350 mg/kg for manganese and from 0.80 to 3.70% for iron. The DTPA-extractable content varied 0.08-1.88 mg/kg for zinc, 0.04-2.40 mg/kg for copper, 0.20-27.7 mg/kg for manganese and 0.50-23.0 mg/ kg for iron. Both total and available micronutrients were higher in the fine-textured soils of Orthents and Fluvents than the coarse-textured soils of Psamments. The total content of micro nutrients increased with increase in clay content and cationexchange capacity (CEC), whereas DTPA-extractable micronutrient increased with increase in organic carbon content and CEC, and decreased with increasing pH and sand content. The total reserve of Zn and eu showed an influence on availability of these respective micro nutrients. Zinc deficiencies were wide spread (47%), followed by Fe (34%) in the cultivated Entisols. These results indicated that zinc is likely to constrain crop production, followed by Fe in Entisols of the Punjab region.